State of the Environment and Its Impacts on the Urban Agriculture of Edible Plants in the City of Lubumbashi - Shengo Lutandula, Michel; Mpanga, Fabien Ilunga (The Global Environmental Engineers, 2022)
This research looked at the state of the environment in the areas where amaranth urban agriculture is practised in the municipality of Katuba, City of Lubumbashi, the Democratic Republic of Congo. Samples of water used for watering, the soil where urban agriculture is practised, and amaranths have been subjected to characterization analyses to look for chemical and microbiological pollutants. These analyses revealed that water and amaranths are polluted from the mineral and microbial standpoint, unlike soil samples. Indeed, water samples contained Paramecia, Entamoeba histolytica’s eggs and colonies of faecal contamination germs, mesophilic flora, and other pathogen germs such as Aeromonas hydrophila and Pseudomonas aeruginosa. As for amaranth samples, their concentrations of cobalt were greater than the value set by the quality standards. The Paramecia, Entamoeba histolytica’s eggs, Escherichia coli, and Klesiella planticola contaminate them. For the above, consuming these amaranths poses health risks to the population. Public authorities must take the necessary measures to organize the practice of urban agriculture of edible plants to bring it up to standard and protect the consumers’ health.